The MiRa scale, a new standardised scale for evaluating nasal deformities before and after septorhinoplasty: A prospective study comparing patient satisfaction and the surgeon's assessment. (26th April 2017) - Radulesco, T.; Penicaud, M.; Santini, L.; Thomassin, J.‐M.; Dessi, P.; Michel, J.
Abstract : Objectives: The objective was to assess the reliability of a new standardised scale for evaluating nasal anomalies in order to compare the surgeon's assessment and patient satisfaction. Design: Monocentric prospective cohort study. Settings: First, we validated the reliability of the MiRa scale; then, we compared the surgeon's assessment and patient satisfaction. Participants: Fifty‐two patients underwent septorhinoplasty surgery and gave their written consent before inclusion. Main outcome measurements: Primary outcome measurement was to validate the reliability of the MiRa scale: two observers analysed all records twice. Intra‐observer reproducibility and interobserver reproducibility were evaluated using the intraclass correlation coefficient (ICC). Secondary outcome measurement was to compare the surgeon's assessment and patient satisfaction: MiRa and ROE (Rhinoplasty Outcome Evaluation) scores were established for each patient prior to and 6 months after surgery. Results: Using the MiRa scale, ICC for intra‐ and interobserver reproducibility was, respectively, 95.4% and 96%, showing no statistical difference ( P =.70, P =.45). Good correlation scores were, respectively, 93% and 92%. Mean ROE scores were 7.1/24 (SD=11.3) before and 19.3/24 (SD=17.3) after surgery ( P <.05). We found an increase in MiRa and ROE scores of +19.75% and +51.25% ( P <.05), respectively. The average postoperative ROE score in the primary septorhinoplasty group was 20.4 (SD=14.4) and 17.2 (SD=23.1) in the secondary septorhinoplasty group ( P <.05). Conclusion: MiRa scale is a reliable, standardised tool to evaluate surgical outcome in septorhinoplasty surgery. It provides an objective and reproducible score. The surgeon's assessment was more critical than patient satisfaction. Patient satisfaction is more difficult to achieve in cases involving a secondary septorhinoplasty.